Effects of Leukocyte-rich platelet-rich plasma and Leukocyte-poor platelet-rich plasma on cartilage in a rabbit osteoarthritis model: Leukocyte-PRP and LP-PRP on osteoarthritis - Zhang, Kefan; Zhang, Chenchen; Ren, Qiang; Wang, Dening; Sun, Li; Wang, Xin; Wang, Yaomin; Shi, Hui (Cellular and Molecular Biology, 2024)
Osteoarthritis is a prevalent chronic disease. One of its primary pathological processes involves the degeneration of articular cartilage. Platelet-rich plasma (PRP) contains cytokines and growth factors that can stimulate the repair and regeneration of articular cartilage tissues. PRP may also slow the progression of osteoarthritis. The purpose of this experiment is to compare the efficacy of Leukocyte poor (LP) - PRP and Leukocyte rich (LR) - PRP in treating rabbit osteoarthritis and to investigate their mechanisms of action. Analyzing the impact of leukocytes on PRP therapeutic effectiveness will provide a valuable clinical reference for the choice of which PRP is better for the treatment of osteoarthritis. A rabbit osteoarthritis model was established by injecting papain into the knee joint cavity, and LP-PRP and LR-PRP were prepared through different centrifugation methods for injection into the knee joint cavity. Eight weeks after injection, rabbit knee cartilage specimens were observed for gross changes, HE staining, senna O-solid green staining, and immunohistochemistry of type II collagen and were quantitatively compared using Pelletier's score, Mankin's pathology score, and ImageJ image processing software. Injection of papain into the knee joint cavity successfully established a rabbit model of osteoarthritis. All three evaluation indexes differed significantly from those of the blank group (P<0.05). LP-PRP and LR-PRP exhibited therapeutic effects when compared with the model group. The two PRP groups had similar gross tissue appearance and pathology (P>0.05). The LR-PRP group had higher collagen type-II expression (P < 0.05) than the LP-PRP group. Both LP-PRP and LR-PRP proved therapeutic for the rabbit papain osteoarthritis model. The difference in leukocyte content between the two groups did not yield different cartilage morphology or other factors by 8 weeks posttreatment. LR-PRP displayed the ability to release more factors relevant to the metabolism of type II collagen than LP-PRP, enabling the preservation of into cartilage collagen content of type II collagen and delaying osteoarthritis progression.